2005
DOI: 10.1093/carcin/bgi130
|View full text |Cite
|
Sign up to set email alerts
|

Frequent activation of the hedgehog pathway in advanced gastric adenocarcinomas

Abstract: The hedgehog pathway plays a critical role in the development of the foregut. Recent studies indicate that the hedgehog pathway activation occurs in the stomach and other gastrointestinal cancers. However, the association of hedgehog pathway activation with tumor stage, differentiation and tumor subtype is not well documented. Here, we report our findings that the elevated expression of hedgehog target genes human patched gene 1 (PTCH1) or Gli1 occurs in 63 of the 99 primary gastric cancers. Activation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
159
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(171 citation statements)
references
References 18 publications
8
159
2
2
Order By: Relevance
“…SHH is active only in stem cells and/or endodermal progenitor in adults (16,23). Recent studies showed that aberrant signaling of this pathway is involved in a variety of human cancers (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The HH pathway essentially consists of PTCH, the motive protein, SMOH, and the transcriptional factors GLI2 and GLI3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SHH is active only in stem cells and/or endodermal progenitor in adults (16,23). Recent studies showed that aberrant signaling of this pathway is involved in a variety of human cancers (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The HH pathway essentially consists of PTCH, the motive protein, SMOH, and the transcriptional factors GLI2 and GLI3.…”
Section: Discussionmentioning
confidence: 99%
“…The HH activation has been observed in other types cancers such as basal cell carcinomas of the skin (6-9), prostate cancer (10,11), lung cancer (12,13), gastrointestinal cancers (14)(15)(16)(17)(18)(19), breast cancer (20,21), and ovarian cancer (22). Although, it is required in liver embryogenesis (14,23), the HH signaling pathway is not well-sustained in the adult liver because of the insufficient HH pathway activity of mature hepatocytes (1,23).…”
mentioning
confidence: 99%
“…Third, different standards have been used to define Hh signaling activation. Some groups use elevated expression of Gli1 as the read-out of Hhsignaling activation (Stecca et al, 2007;Bhattacharya et al, 2008) whereas others assess expression of several Hh target genes, such as Gli1, PTCH1, sFRP1 and HIP (Thayer et al, 2003;Karhadkar et al, 2004;Ma et al, 2005;Huang et al, 2006;Lee et al, 2007). Similarly, some groups use only immunohistochemistry to detect Hh-signaling activation (Kubo et al, 2004;Liao et al, 2009) whereas most studies use multiple approaches.…”
Section: Activation Of Hh Signaling In Extracutaneous Tumorsmentioning
confidence: 99%
“…Although the control for cyclopamine treatment is hard to find, tomatidine has been used as a control in Hedgehog signaling in human cancer L Yang et al many studies (Karhadkar et al, 2004;Huang et al, 2006;Liao et al, 2009). If the cyclopamine effect is specific, overexpression of the downstream transcription effector (Gli1 or Gli2) in the sensitive cells should render the cells resistant to cyclopamine (Ma et al, 2005). As increasing evidence indicates that Hh signaling requires stromal components in human cancers, in vitro studies on Hh signaling in human cancer should be backed up with in vivo data.…”
Section: Small-molecule Modulators Of Hedgehog Signalingmentioning
confidence: 99%
“…Substantial evidence has shown that the Shh pathway is crucial to the development and homeostasis of gastric glands. In addition, abnormal activation of the Shh pathway has been found toresult in gastric cancer (12)(13)(14).The aim of the present study was to investigate the effects of metformin on the regulation of the Shh signaling pathway in gastric cancer cells. The expression levels of Shh, Glioma associated oncogene (Gli)-1, Gli-2 and Smoothened (SMO) were examined using western blot and reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analyses.…”
mentioning
confidence: 94%